Method for obtaining stress distribution of chemically strengthened aluminosilicate glass, and method for manufacturing chemically strengthened aluminosilicate glass

By measuring stress distributions for tempered glasses under various conditions and deriving related parameters, the method accurately calculates deep-side stress distributions in tempered glass, addressing the challenge of varying reinforcement conditions and improving manufacturing efficiency.

JP7648382B2Active Publication Date: 2025-03-18AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020539330
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-29
Filing Date
2019-08-14
Publication Date
2025-03-18
Estimated Expiration
2039-08-14

AI Technical Summary

Technical Problem

Existing methods for manufacturing tempered glass struggle with accurately measuring stress distribution on both the surface and deep sides of the glass, leading to errors when reinforcement conditions vary.

Method used

A method involving the measurement of stress distributions for multiple tempered glasses under different conditions, followed by the derivation of parameters that relate the surface and deep-side stress distributions, allowing for the calculation of deep-side stress distributions based on surface measurements.

Benefits of technology

This approach improves the accuracy of calculating stress distributions on the deep side of tempered glass, reducing errors caused by varying reinforcement conditions and enhancing productivity by minimizing the need for separate measurements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648382000016
    Figure 0007648382000016
  • Figure 0007648382000017
    Figure 0007648382000017
  • Figure 0007648382000018
    Figure 0007648382000018
Patent Text Reader

Abstract

This method for obtaining the stress distribution of tempered glass includes, as a preliminary step, measuring the stress distribution of a plurality of tempered glasses, including tempered glasses with different tempering conditions, and deriving a parameter indicating the relationship between the first stress distribution and the second stress distribution based on the measurement result of a first stress distribution closer to the surface of the glass than the glass depth at which the stress distribution bends, and the measurement result of a second stress distribution closer to the deeper side of the glass than the glass depth, and a step of using the parameter to obtain the stress distribution of the tempered glass to be measured, wherein the step of obtaining the stress distribution includes the steps of measuring the first stress distribution of the tempered glass to be measured, and calculating the second stress distribution based on the parameter.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to chemistry reinforcement Aluminosilicate How to obtain the stress distribution in glass; chemistry reinforcement Aluminosilicate The present invention relates to a method for producing glass. [Background technology]

[0002] In electronic devices such as mobile phones and smartphones, glass may be used for the display unit or the housing body. In this case, so-called tempered glass is used, in which a surface layer (ion exchange layer) is formed on the glass surface by ion exchange, in order to increase the strength of the glass.

[0003] In recent years, lithium-containing aluminosilicate glass has been widely used. Also, chemically strengthened lithium-containing aluminosilicate glass is known in which both ion exchange between lithium ions in the glass and sodium ions in a molten salt and ion exchange between sodium ions in the glass and potassium ions in a molten salt are performed.

[0004] The stress distribution of tempered glass containing lithium and having undergone two types of ion exchange exhibits a bending characteristic at a certain glass depth (DOL_TP). The refractive index distribution exhibits the characteristic shown in Figure 3. However, in such tempered glass, it is difficult to measure the stress distribution on the glass surface side beyond DOL_TP and the stress distribution on the glass deeper side beyond DOL_TP using the same device.

[0005] In the manufacturing process of tempered glass, if the stress distribution on the surface side of the glass beyond DOL_TP and the stress distribution on the deeper side of the glass beyond DOL_TP are measured for each piece of tempered glass using different measuring devices, the measurement time will be long and productivity will be reduced.

[0006] Therefore, in the manufacturing process of tempered glass, only the stress distribution on the glass surface side beyond DOL_TP was measured, and for the stress distribution on the glass deeper side beyond DOL_TP, the stress distribution of tempered glass manufactured under the same tempering conditions was measured in advance and calculated based on the results of the previous measurement. This eliminated the need to measure the stress distribution on the glass deeper side beyond DOL_TP during the manufacturing process of tempered glass, thereby reducing the measurement time. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2018 / 056121 Summary of the Invention [Problem to be solved by the invention]

[0008] However, with the above method, if the tempering conditions vary, errors will occur in the calculation results of the stress distribution deeper in the glass than the DOL_TP, so there was a need to improve the accuracy.

[0009] The present invention has been made in view of the above points, chemistry reinforcement Aluminosilicate The purpose of this study is to improve the accuracy of calculation of stress distribution in glass deeper than DOL_TP. [Means for solving the problem]

[0010] Books chemistry reinforcement Aluminosilicate The method for obtaining the stress distribution in glass is as follows: A chemical compound containing lithium that has two types of ion exchange and a curved stress distribution. reinforcement Aluminosilicate A method for acquiring a stress distribution of glass, comprising: measuring, as a preliminary step, the stress distribution of a plurality of pieces of tempered glass including tempered glass pieces having different tempering conditions; and acquiring a first stress distribution on the glass surface side relative to a depth of the glass where the stress distribution is bent. σ 1 (x, Bn) Measurement results and a second stress distribution on the glass deeper side than the glass depth σ 2 (x, Cm, CT) multiple Based on the measurement results, Fit Cm as a linear or higher function of Bn, The relationship between the first stress distribution and the second stress distribution is shown. The above function Step of deriving S10 and measurement Step 2: Obtaining the stress distribution of the tempered glass to be determined S20 and determining the stress distribution. S20 The first stress distribution for the tempered glass to be measured σ 1 (x, Bn) and measuring The first stress distribution σ measured in the step of measuring the first stress distribution 1 Using Bn in (x, Bn) and the function indicating the relationship between the first stress distribution and the second stress distribution, the second stress distribution σ 2 A step of obtaining Cm in (x, Cm, CT), and the first stress distribution σ 1 (x, Bn) and the above σ 2 A step of synthesizing (x, Cm, CT) and determining a CT at which the integral value of the stress distribution after synthesis (x=0 to t / 2, t is the thickness of the tempered glass to be measured) becomes zero; The requirement is that the Effect of the Invention

[0011] According to the disclosed technology, chemistry reinforcement Aluminosilicate In glass, the calculation accuracy of the stress distribution on the deeper side of the glass than DOL_TP can be improved. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram illustrating a stress distribution in a depth direction of strengthened glass. [Diagram 2] 1 is an example of a flowchart showing a method for acquiring stress distribution of strengthened glass. [Diagram 3] FIG. 2 is a diagram illustrating a refractive index distribution in the depth direction of strengthened glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same components are denoted by the same reference numerals, and duplicated explanations may be omitted.

[0014] Fig. 1 is a diagram illustrating stress distribution in the depth direction of tempered glass. In Fig. 1, CS2 is the stress value at the outermost surface, CS_TP is the stress value at the position where the stress distribution bends, and CT is the stress value at the deepest part of the glass (i.e., the center in the sheet thickness direction). In addition, DOL_TP is the glass depth at the position where the stress distribution bends, DOL_zero is the glass depth at which the stress value becomes zero, and DOL_tail is the glass depth at which the stress value becomes the same value as CT.

[0015] In this specification, the stress distribution on the glass surface side of DOL_TP is referred to as a first stress distribution, and the stress distribution on the glass deeper side of DOL_TP is referred to as a second stress distribution.

[0016] It is difficult to measure the first stress distribution and the second stress distribution with high accuracy using the same measurement principle. Therefore, when it is necessary to measure the first stress distribution and the second stress distribution with high accuracy, it is necessary to measure them separately using different measurement principles. An example of the measurement principle for the first stress distribution and the second stress distribution will be described below.

[0017] The first stress distribution can be measured, for example, by a photoelastic technique using the optical waveguide effect to propagate light along the glass surface.

[0018] More specifically, two types of light components (P-polarized and S-polarized) of light propagated along the glass surface, which vibrate parallel and perpendicular to the exit surface, are converted into two types of bright line trains, each having at least two or more bright lines. The two types of bright line trains are then imaged by an imaging element such as a CCD (Charge Coupled Device), and a refractive index distribution from the surface of the strengthened glass in the depth direction corresponding to the two types of light components is calculated from the positions of the at least two or more bright lines in each of the two types of bright line trains. A first stress distribution from the surface of the strengthened glass in the depth direction can then be calculated based on the difference in the refractive index distributions of the two types of light components and the photoelastic constant of the glass.

[0019] The first stress distribution can be measured, for example, using a glass surface stress meter FSM-6000LE manufactured by Orihara Manufacturing Co., Ltd. However, the first stress distribution may be measured by any method other than the above, for example, the well-known inverse WKB method (see, for example, U.S. Pat. No. 9,140,543). Note that, in principle, measurements using the optical waveguide effect can only measure the portion where the refractive index decreases from the glass surface toward the depth of the glass. Therefore, this method can only be used to measure the first stress distribution.

[0020] The second stress distribution can be measured, for example, by using the principle of photoelastic stress measurement that utilizes the polarization phase difference of laser light and scattered light.

[0021] More specifically, the polarization phase difference of the laser light is varied by one or more wavelengths relative to the wavelength of the laser light, and the scattered light emitted by the laser light with the varied polarization phase difference being incident on the strengthened glass is captured multiple times at a predetermined time interval to obtain multiple images.Then, the periodic luminance change of the scattered light is measured using the multiple images obtained, and the phase change of the luminance change is calculated, and the second stress distribution can be calculated based on the phase change.

[0022] The second stress distribution can be measured, for example, using a scattered light photoelastic stress meter SLP-1000 manufactured by Orihara Seisakusho. However, the second stress distribution may be measured by any method other than the above. The second stress distribution may be measured, for example, using a scattered light photoelastic stress meter SLP-2000 manufactured by Orihara Seisakusho, a glass cross-sectional stress meter SCALP-04 or SCALP-05, or a birefringence imaging device abrio manufactured by CRi, Inc., USA. In the case of measurement using scattered light, due to its principle, the reflected light or scattered light on the glass surface overlaps with the scattered light from inside the glass and interferes, resulting in low measurement accuracy near the glass surface. Therefore, this method can be used only to measure the second stress distribution.

[0023] Incidentally, a manufacturing process of tempered glass may include a process of measuring a first stress distribution and a second stress distribution and determining whether or not to ship the glass based on the first stress distribution and the second stress distribution. In this case, if the first stress distribution and the second stress distribution are measured for each piece of tempered glass using different measuring devices, the measurement time will be long and productivity will decrease.

[0024] Therefore, in this embodiment, for a plurality of tempered glasses with different tempering conditions, the first stress distribution and the second stress distribution are measured in advance by an appropriate measuring method, respectively, to create a database, and parameters indicating the relationship between the first stress distribution and the second stress distribution are derived. Then, in the manufacturing process of the tempered glass, only the first stress distribution is measured, and the second stress distribution is calculated based on the parameters derived in advance. This will be described in detail below with reference to FIG. 2.

[0025] FIG. 2 is an example of a flowchart showing a method for acquiring the stress distribution of tempered glass. Step S10 in FIG. 2 is a preparatory step performed independently of the tempered glass manufacturing process. In step S10, first, the stress distribution is measured for a plurality of tempered glasses including tempered glasses with different tempering conditions. Specifically, for example, the first stress distribution is measured using FSM-6000LE, and the second stress distribution is measured using SLP-1000. Then, based on the measurement results of the first stress distribution and the second stress distribution, a parameter indicating the relationship between the first stress distribution and the second stress distribution is derived.

[0026] The first stress distribution can be expressed as, for example, σ1(x, Bn). Here, x indicates the position in the depth direction of the tempered glass, and Bn means a fitting parameter. Bn may be multiple. The first stress distribution can be approximated by a straight line, for example. In this case, the first stress distribution can be expressed (fitted) as σ1(x, Bn)=CS2+a·x, where CS2 is the stress value at the outermost surface, and a is the gradient of the stress at the tempered glass surface. Here, B1=CS2, B2=a.

[0027] The first stress distribution may be expressed by any fitting function as long as it is a linear or higher function and uses two or more parameters. The fitting function σ1(x, Bn) used for fitting the first stress distribution in step S10 may be, for example, σ1(x, Bn)=B1·erfc(B2·x). Also, σ1(x, Bn)=B1 / B2 2 (x-B2) 2 Alternatively, σ1(x, Bn)=B1+B2·x+B3·x 2 +B4·x 3 In either case, B1=CS2 may be set, where erfc is a well-known complementary error function.

[0028] Moreover, the second stress distribution can be expressed as, for example, σ2(x, Cm, CT). Here, x indicates a position in the depth direction of the strengthened glass, and Cm indicates a parameter derived in step S10. There may be a plurality of parameters Cm (C1, C2, ...). The parameter Cm can be derived for each thickness of the strengthened glass, for example. Alternatively, the thickness of the strengthened glass may be included in the parameters.

[0029] Based on the measurement results of the first stress distribution and the second stress distribution, a correlation diagram between CS2 and Cm and a correlation diagram between a and Cm can be obtained. Using these, the relationships between CS2, a, and Cm can be derived. For example, Cm can be expressed as a linear function of CS2 and a. If necessary, Cm may be expressed as a quadratic or higher degree function of CS2 and a. In other words, Cm can be a linear or higher degree function of Bn.

[0030] Next, in step S20, the stress distribution of the tempered glass to be measured is obtained. Step S20 can be included in the manufacturing process of tempered glass.

[0031] Step S20 includes step S201 of measuring a first stress distribution for the strengthened glass to be measured, and step S202 of calculating a second stress distribution based on the parameter Cm derived in step S10.

[0032] In step S201, a first stress distribution is measured for the tempered glass to be measured, for example, using FSM-6000LE. CS2 and a can be obtained by FSM-6000LE.

[0033] In step S202, the second stress distribution is calculated (the second stress distribution is not measured). When the second stress distribution is represented by σ2(x, Cm, CT), Cm is a linear or higher function of CS2 and a, but since CS2 and a are known in step S201, Cm is also known. Then, since the only unknown value in σ2(x, Cm, CT) is CT, the second stress distribution can be calculated by finding CT in step S202.

[0034] CT can be determined by combining the first stress distribution measured in step S201 with σ2(x, Cm, CT) so that the integral value (x=0 to t / 2, t is the plate thickness of the tempered glass to be measured) of the combined stress distribution becomes zero. This is based on the fact that the sum of stresses is generally zero if no external force is applied.

[0035] By the above integration, there are no unknown values ​​in σ2(x, Cm, CT), and the second stress distribution is calculated. This allows the stress distribution of the entire tempered glass to be obtained by combining the first stress distribution and the second stress distribution. The shipping decision of the tempered glass can be made based on the obtained entire stress distribution (the first stress distribution and the second stress distribution).

[0036] In this manner, in the present embodiment, as a preliminary step, a parameter indicating a relationship between the first stress distribution and the second stress distribution is derived based on the stress distribution measurement results for a plurality of tempered glasses including tempered glasses with different tempering conditions, and the second stress distribution is calculated based on the derived parameter.

[0037] This makes it possible to reduce errors caused by variations in tempering conditions and improve the calculation accuracy of the second stress distribution, compared with the case where parameters are derived based on the stress distribution of tempered glass measured in advance under the same conditions. In particular, since errors are more likely to occur as the number of tempering processes increases, the merit of adopting the method for obtaining the stress distribution of tempered glass according to the present embodiment becomes greater. [Examples and Comparative Examples] First, step S10 shown in Fig. 2 will be described. Tempered glass was produced by chemically tempering lithium-containing aluminosilicate glass having a plate thickness of 0.7 mm under the four tempering conditions (conditions 1 to 4) shown in Table 1. Then, for each tempered glass, a first stress distribution was measured using FSM-6000LE (manufactured by Orihara Seisakusho: hereinafter referred to as FSM) and a second stress distribution was measured using SLP-1000 (manufactured by Orihara Seisakusho: hereinafter referred to as SLP) to obtain the characteristic values ​​of the stress distribution shown in Fig. 1. The obtained characteristic values ​​are shown in Table 2.

[0038] [Table 1]

[0039] [Table 2] Furthermore, the parameters are derived based on the measurement results of the characteristic values ​​shown in Table 2. The measurement values ​​of the first stress distribution measured by FSM were fitted with σ1(x, Bn) = CS2 + a·x.

[0040] In the conventional method, the second stress distribution measured by SLP is fitted to the measurement results by equation (1). Therefore, for comparison, the measurement results (second stress distribution) by SLP of four tempered glasses chemically tempered under conditions 1 to 4 were fitted to equation (1) to obtain the average parameters CS0 and c (Comparative Example in Table 3).

[0041]

number

[0042]

number

[0043] [Table 3] Next, step S20 in FIG. 2 will be described. Eight types of samples with different concentrations of reinforcing salt were prepared, and the first stress distribution was measured by FSM. Then, the CT was obtained from the first stress distribution measured by FSM and the second stress distribution derived from the parameters of the comparative example in Table 3 (Comparative Example in Table 4). Also, the CT was obtained from the first stress distribution measured by FSM and the second stress distribution derived from the parameters of the example in Table 3 (Example in Table 4). For comparison, the CT was also measured by SLP, and is listed in Table 4 together with the CTs obtained in the comparative example and example. Also, the correlation coefficient between the actual measurement value and the comparative example, and the correlation coefficient between the actual measurement value and the example are listed in Table 4.

[0044] [Table 4] From the correlation coefficients shown in Table 4, it was confirmed that the examples had a higher correlation with the actual measured values ​​than the comparative examples.

[0045] In this way, by incorporating the FSM measurement values ​​for tempered glass with different tempering conditions as part of the parameters in the fitting function σ2, it becomes possible to calculate the second stress distribution with high accuracy even if the tempered glass to be measured changes.

[0046] In this example, in step S10, the concentration of the strengthening salt is changed as an example of changing the strengthening conditions of the strengthened glass. However, the thickness of the glass or the strengthening temperature and time may also be changed, and there is no limit to the conditions that can be changed.

[0047] In addition, the concentration of the strengthening salt may be increased or decreased when new strengthened glass is strengthened repeatedly, as in mass production. For example, a mixture of KNO3, NaNO3, and LiNO3 salts was used for the second chemical strengthening, but a mixture of KNO3, NaNO3, and LiNO3 may also be used.

[0048] When the sheet thickness of the glass is changed, Cm can be a linear or higher function of the sheet thickness, and for example, the second stress distribution may be fitted by equation (3). The sheet thickness may be measured simultaneously with the stress measurement in step S20.

[0049]

number

[0050]

number

[0051]

number

[0052]

number

[0053]

number

[0054] This international application claims priority based on Japanese Patent Application No. 2018-160215, filed on August 29, 2018, the entire contents of which are incorporated herein by reference.

[0055] Although the preferred embodiments have been described in detail above, the present invention is not limited to the above-described embodiments, and various modifications and substitutions can be made to the above-described embodiments without departing from the scope of the claims.

Claims

1. A method for obtaining a stress distribution of chemically strengthened aluminosilicate glass that contains lithium and has a curved stress distribution due to two types of ion exchange, comprising: Step S10: as a preliminary step, measuring stress distributions for a plurality of pieces of tempered glass including tempered glass pieces having different tempering conditions, fitting Cm as a first or higher order function of Bn based on a plurality of measurement results of a first stress distribution σ 1 (x, Bn) on the glass surface side of a glass depth at a position where the stress distribution bends and a plurality of measurement results of a second stress distribution σ 2 (x, Cm, CT) on the glass deeper side of the glass depth, and deriving the function showing a relationship between the first stress distribution and the second stress distribution; A step S20 of obtaining a stress distribution of the strengthened glass to be measured, The step S20 of determining the stress distribution includes: Measuring the first stress distribution σ 1 (x, Bn) for the strengthened glass to be measured; determining Cm in the second stress distribution σ 2 (x, Cm, CT) using Bn in the first stress distribution σ 1 (x, Bn) measured in the step of measuring the first stress distribution and the function indicating the relationship between the first stress distribution and the second stress distribution; a step of combining the first stress distribution σ 1 (x, Bn) and the σ 2 (x, Cm, CT) and determining a CT at which an integral value (x=0 to t / 2, t is a plate thickness of the tempered glass to be measured) of the combined stress distribution becomes zero; A method for obtaining stress distribution in chemically strengthened aluminosilicate glass, comprising:

2. In the step S10 of deriving the function, the first stress distribution is expressed as σ 1 2. The method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to claim 1, characterized in that fitting is performed using (x, Bn) = CS2 + a x (where CS2 is the stress value of the outermost surface of the strengthened glass, and a is the stress gradient at the surface of the strengthened glass).

3. In the step S10 of deriving the function, the first stress distribution is expressed as σ 1 (x, Bn)=B 1 ・erfc(B 2 The method for obtaining stress distribution of chemically strengthened aluminosilicate glass according to claim 1, characterized in that fitting is performed using x).

4. In the step S10 of deriving the function, the first stress distribution is expressed as σ 1 (x, Bn)=B 1 / B 2 2 · (x-B 2 ) 2 The method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to claim 1, characterized in that fitting is performed by:

5. In the step S10 of deriving the function, the first stress distribution is expressed as σ 1 (x, Bn)=B 1 +B 2 ・x+B 3 ・x 2 +B 4 ・x 3 The method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to claim 1, characterized in that fitting is performed by:

6. B 1 The method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to claim 3, wherein CS2 is the stress value of the outermost surface of the strengthened glass.

7. The method for acquiring stress distribution in chemically strengthened aluminosilicate glass according to claim 2 , wherein Cm is a linear or higher function of CS2 and a.

8. The σ 2 The method for acquiring stress distribution in chemically strengthened aluminosilicate glass according to claim 2, characterized in that equation (2) is used for (x, Cm, CT). [0025]

9. 9. The method for acquiring stress distribution in chemically strengthened aluminosilicate glass according to claim 1, wherein in step S10 of deriving the function, the function is derived by preparing a plurality of strengthened glasses including strengthened glasses having different strengthening conditions, the plurality of strengthened glasses being prepared by changing at least the salt concentration of the strengthening salt.

10. The method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to any one of claims 1 to 9, characterized in that in step S10 of deriving the function, for a plurality of tempered glasses including tempered glasses having different tempering conditions, glass having at least a different plate thickness is prepared to derive the function.

11. The σ 2 The method for acquiring stress distribution in chemically strengthened aluminosilicate glass according to claim 2, characterized in that equation (5) is used for (x, Cm, CT). [0050]

12. The σ 2 (x, Cm, CT) is expressed by the formula (6) (where t CS is the reinforcement time, T CS The method for obtaining stress distribution of chemically strengthened aluminosilicate glass according to claim 2, characterized in that x is the strengthening temperature. [006]

13. The σ 2 The method for acquiring stress distribution in chemically strengthened aluminosilicate glass according to claim 1, characterized in that equation (7) is used for (x, Cm, CT). [0070] 14. A method for producing chemically strengthened aluminosilicate glass, comprising the steps of:

14. A method for producing chemically strengthened aluminosilicate glass, comprising the steps of: making a shipping decision based on the first stress distribution and the second stress distribution acquired by the method for acquiring stress distribution of chemically strengthened aluminosilicate glass according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Glass with a compression surface for consumer use

    JP2011527661A

  • Surface stress measurement method and surface stress measurement device

    JP2016142600A

  • Methods for producing ion-exchangeable glasses

    US20130233020A1

  • Methods of characterizing ion-exchanged chemically strengthened glasses containing lithium

    US20170082577A1

  • Stress measuring device for tempered glass, stress measuring method for tempered glass, method for manufacturing tempered glass, and tempered glass

    WO2018056121A1